Sugar labeling information and online marketing strategies for hand-shaken tea drinks in northern Taiwan - Liu, Chi-Hsuan; Wong, Te-Chih; Chung, Mei; Bai, Chyi-Huey; Chen, Yi-Chun (Frontiers in Nutrition, 2023)
Background: Sugar-sweetened beverages are the main cause of excessive sugar intake and increased health risks. Food companies usually use social media to market SSBs in order to increase consumers' purchase intentions. To reduce excessive added sugar consumption from hand-shaken tea drinks, Taiwan has implemented a mandatory policy requiring clear sugar content labeling. This study aimed to investigate the sugar label information and online marketing strategies for hand-shaken tea drinks in northern Taiwan.In this cross-sectional study, content analysis was employed to investigate the sugar labeling information and the current situation of online marketing in hand-shaken tea drink brands based in northern Taiwan. 72 hand-shaken tea drink brands were initially visited for sugar labeling methods; excluding those without complete labeling or customizable sugar levels, 60 brands were selected for further data collection. The sugar and energy contents in 1581 hand-shaken tea drinks were recorded and calculated. Subsequently, the sugar contents were assessed in accordance with World Health Organization sugar recommendations (25g/day), Warning Label criteria, and Taiwan's regulations for low-sugar packaged beverages. Seven brands that had high online impressions were further selected and their marketing strategies in 560 Facebook posts were analyzed. Results: The presentation methods of labeling varied among the 60 brands, and only 42 brands had obvious and easily accessible labeling. The most common labeling presentation method was posters (n=28). After converting the sugar content of half-sugar and low-sugar hand-shaken tea drinks, it was found that 60.2% of half-sugar beverages and 13.0% of low-sugar beverages exceeded 25g of sugar per cup. Over 90% of brands had Facebook and Instagram accounts. The top marketing strategies for tea drink brands on Facebook were specific beverage information, brand information, and nutrition and health marketing. Most posts promoted sugar-sweetened beverages. Conclusions: Not all hand-shaken tea drink brands in this study followed Taiwan's labeling regulations. Moreover, high sugar contents in handshaken tea drinks labeled as half-sugar and low-sugar could potentially lead people to unconsciously consume excessive amounts of sugar. Future research should explore the impact of online marketing strategies on SSBs consumption behavior and ways to mitigate it among the Taiwanese public.